Enterprise systems in print production workflow / Muhammad Yusuf Masod, Siti Farhana Zakaria and Sebastianus Adi Susanto - Masod, Muhammad Yusuf Masod; Zakaria, Siti Farhana Zakaria; Susanto, Sebastianus Adi Susanto (Universiti Teknologi MARA, 2018)
Operations in a printing company are complex, whereby numerous entities, resources, and processes are involved in completing a single job. The parties in a transaction often include customers, material suppliers, external service providers, and shipping/delivery companies. On the other hand, production resources consist of equipment, employees, and materials, whereas production processes comprise prepress, press, and post press activities. Typically, the cycle of a job begins with sales and customer service, and ends with the accounting department generating an invoice and processing the payment. In between, other departments perform services that are critical to the job cycle, but are not directly involved with production. The introduction of enterprise systems in print production workflow is to assist and improve business operations. Web-to-print system, Print Management Information System (MIS), and PDF workflow system are recognized as the most important systems in print production workflow. To achieve maximum benefits, assessing the needs and choosing the right print production system are profound planning activities before commencing the initial implementation phase.